Konsep Dasar dan Teori Pendidikan Agama Islam - I Wayan Sritama (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2019)
The purpose of education in general is to form good people. But the purpose of education will be difficult to achieve if it does not pay attention to the steps in learning in education. There are several concepts of Islamic religious education developed in Indonesia, one of which is the basic concept of Islamic religious education sourced from Imam Al Ghazali. The success of education and learning with the concepts and theories of Islamic religious education is characterized by changes in both cognitive and affective. The Role of Islamic Education in shaping the personality of students should rest on the condition or type of students and the theme to be delivered. So that the material to be delivered is easily accepted by students. However, what is equally important is the existence of exemplary and the ability of educators to provide motivation to learn to proceed towards commendable behavior which is the basic goal of Islamic education.